ANALISIS KEMAMPUAN PASSING BAWAH BOLA VOLI PADA SISWA SDN MANGASA - Achmad Karim (MACCA : Science-Edu Journal, 2026)
This quantitative research aims to determine the volleyball underhand passing ability of students at Mangasa Elementary School. The population of this study was all students at Mangasa Elementary School. Purposive sampling was used to determine the sample size, thus reflecting the total population of 30 students at Mangasa Elementary School. The data collection technique used was an underhand passing test for the students at Mangasa Elementary School. The results of the study on the underhand passing ability of the 30 students at Mangasa Elementary School showed that out of 30 students, 2 (6.67%) were in the excellent category, 10 (33.33%) were in the good category, 8 (26.67%) were in the fair category, 7 (23.33%) were in the poor category, and 3 (10.00%) were in the poor category. Based on the research results and discussion, it can be concluded that the volleyball underhand passing ability of the students at Mangasa Elementary School is categorized as "good."